Pelatihan Penggunaan Google Classroom untuk Menunjang Keterampilan Guru dalam Mengelola Pembelajaran Daring di Masa Pandemi Covid-19 - Meidi Saputra (Universitas Muhammadiyah Semarang, 2022)
The role of teachers in managing bold learning during the Covid-19 pandemic is a necessity. One of the media that teachers can use in managing bold learning is Google Classroom. To be able to manage this learning, teachers need to be given training to support their skills. The purpose of this community service is to provide skills to teachers in managing learning using Google Classroom during the Covid-19 pandemic. The method of implementing this service consists of 1) Situation Analysis, 2) Service Program Planning, 3) Service Implementation and 4) Service Evaluation. The result of knowledge from this community service is that the teacher gets about the Google Classroom learning media so that it can make it easier for them to carry out bold learning during the Covid-19 pandemic. Then the teacher also has a view in managing learning during the Covid-19 pandemic, starting from lesson planning to learning evaluation through Google Classroom learning media.